Enforcement of the Results of Online Alternative Dispute Resolution Methods An Analytical Study on Automated Enforcement Strategies - Reza Maboudi Neishabouri; SeyedAlireza Rezaee (حقوق فناوریهای نوین, 2021)
One of the most important developments in dispute resolution law is the emergence of online dispute resolution methods. There are ambiguities and legal issues regarding said methods due to their specific characteristics and occurrence in cyberspace. One of the challenges of these methods is how to enforce the results because the ordinary or traditional methods of enforcing final dispute resolution documents are not helpful in this field. Due to the high importance of the enforcement of final documents in the validity and acceptability of each dispute resolution method, the legal doctrine and e-commerce activists: predicted and implemented solutions about automatic enforcement of results of online dispute resolution methods without the need for the recourse to courts or other authorities. The present study has examined the strategies of automatic enforcement of ODR final documents in the following topics: "Monetary Enforcement Mechanisms", "Domain Name Resolution Enforcement Strategies", and "Automatic Enforcement Based on Blockchain Technology". The present article concludes that supporting and promoting online dispute resolution methods and strategies for automatic enforcement of ODR final documents is the most critical and fundamental step in reducing the workload of the courts and other legal authorities. At the same time, such a goal is not achievable without the legislature's support and the approval of the corresponding laws. In this regard, the Iranian Legislature is advised to draft and enact integrated and comprehensive rules in the area.